1998
DOI: 10.1103/physrevlett.80.417
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Efficiency of a DNA-Based Computation

Abstract: DNA-based computing uses the tendency of nucleotide bases to bind (hybridize) in preferred combinations to do computation. Depending on reaction conditions, oligonucleotides can bind despite noncomplementary base pairs. These mismatched hybridizations are a source of false positives and negatives, which limit the efficiency and scalability of DNA-based computing. The ability of specific base sequences to support error-tolerant Adleman-style computation is analyzed, and criteria are proposed to increase reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 7 publications
(18 reference statements)
0
39
0
Order By: Relevance
“…Later work on error-prevention has confirmed that the reduction will be orders of magnitude smaller [6]. Based on combinatorial constraints, [14] combinatorially obtained some theoretical lower bounds and upper bounds of the number of equilength DNA strands.…”
Section: Dna-based Memory Capacitymentioning
confidence: 99%
“…Later work on error-prevention has confirmed that the reduction will be orders of magnitude smaller [6]. Based on combinatorial constraints, [14] combinatorially obtained some theoretical lower bounds and upper bounds of the number of equilength DNA strands.…”
Section: Dna-based Memory Capacitymentioning
confidence: 99%
“…As we have discussed in the properties of DNA, the primary structure, i.e., the sequence or the order of nucleotides, of DNA primarily determines its secondary and tertiary structures, thus it is of significance to design sequence which gives the desired bulk material properties. Meanwhile, although two complementary DNA strands achieve their minimum energy state when they hybridize in the perfectly aligned configuration, DNA hybridization does not occur without error (Deaton et al 1998). In addition, undesired interactions can occur between two strands as well as within a single strand.…”
Section: Sequence Designmentioning
confidence: 99%
“…Design of a pair of equal-length sequences is essentially an optimization problem with the minimization of undesirable (e.g., off-alignment) interactions as the objective function. For instance, in the work by Lin et al (Lin et al 2004b), DNA sequence was generated by incorporating into the algorithm the following considerations: minimization of undesired interactions among strands and potential secondary structures, thermodynamic stability of the hybridized sequence pairs (e.g., GC content, terminal sequences, and hairpin structures (Lin et al 2004b, SantaLucia & Hicks 2004), and initiation of branch migration (e.g., length of sticky ends) (Deaton et al 1998, Felsenfeld & Miles 2003. C-rich domain can be incorporated where it is desirable to have pH responsiveness (Cheng et al 2009).…”
Section: Sequence Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Several error detection and fault tolerance methods have been established to increase the accuracy of computation [14][15][16][17][18]. Among them, Deaton et al [19] studied the errors associated with imperfect hybridization (i.e., false positive and false negative ligations). The authors pointed out that these errors depended largely on the reaction conditions of the hybridization, in particular on temperature.…”
Section: Biocomputing For Np-complete Problemsmentioning
confidence: 99%